Design of School Bell Scheduling Application Based on Arduino Uno on MTs Babussalam Simandolak - Dede Setiawan; Febri Haswan; Jasri Jasri (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2024)
MTs Babussalam Simandolak which is located in Tebing Tinggi Simandolak Village, Benai District, Kuantan Singingi Regency. MTs Babusalam Simandolak has problems related to the scheduling of picket teachers and bell information which is still operated manually, where officers often have difficulty ringing the bell during changing hours because those who are often on duty are also teaching teachers, making the picket teachers have to go back and forth to set the bell and return to teaching. Then, the recapitulation data on teacher attendance in carrying out the picket schedule (picket implementation report) is still not well coordinated, there is often a buildup of data, data is suddenly lost, and sometimes people even forget where to put the picket book. Furthermore, the problem with bell information which is still manual causes inefficient time between study hours and students' break times. With this research, MTs Babussalam Simandolak can easily inform the change of each subject or other activity automatically without having to ring the bell and the scheduling process, Reporting already uses computerization. This school bell has used running text as a medium of information for teachers or employees at MTs Babussalam Simandolak.